Financial literacy and personal financial management assessment among students in border area of indonesia-timor leste - Yohanis Ndapa Deda; Hermina Disnawati; Ando Missa (IJHCM (International Journal of Human Capital Management), 2022)
Financial literacy has become a global trend and the need for individuals to take responsibility for their finances. Still, financial literacy and financial management have not yet become a course in some universities, especially Timor University, which lies in the border area of Indonesia-Timor Leste (BAITL). Economic literacy and student financial management levels need to be analyzed because they relate to expenditure, income, credit, savings, and investments. This study aimed to evaluate financial literacy level and personal financial management level among college students in BAITL. This research includes quantitative descriptive analysis. Data was collected using a questionnaire from 165 undergraduate college students in the mathematics education department of a public university in East Nusa Tenggara (NTT), Indonesia. The results showed that the total average level of student financial literacy (SFL) was 67.48%. The comprehensive middle student personal finance management (SPFM) is 57.34%, and the estimated result of the linear regression model is SPFM = 3.158 + 0.338SFL. These results were significant at a degree of freedom of 163 and Alpha 5% of the t-test results. From the study results, it can conclude that the personal financial management of students of mathematics education is still low. The level of financial literacy of students in the border area includes less literate. If the SFL is a fixed value, then each increase in SFL of 1 unit will increase SPFM 0.338.